RIVER MANAGEMENT BASED ON PHYSICAL CHEMICAL PARAMETERS OF WATER QUALITY IN WAI BATU GAJAH, AMBON CITY - Tuhumury, Novianty; Selanno, Debby A. J.; Angwarmase, Yohanes (Universitas Mataram, 2025)
The increase in population has an impact on the water quality of several rivers in Ambon City, one of which is Wai Batu Gajah. This study aims to analyze the physical chemical parameters of the waters, describe community activities and management efforts that have been carried out, and recommend management strategies and programs in Wai Batu Gajah. The research was conducted in Wai Batu Gajah, Ambon City in May-June 2023 at 7 observation stations. The physical and chemical parameters measured included odor, color, width, height, substrate type, temperature, TSS, current velocity, pH, DO, BOD, and ammonia. The method of collecting data on physical and chemical parameters was carried out directly in the field, then analyzed in the laboratory of the Maluku Province Health and Calibration Center. Data on community activities were obtained through interviews using questionnaires to 35 respondents. The value of the physical and chemical parameters of the waters was referred to the river quality standards. Strategies and management programs were analyzed using SWOT and TOWS methods. The results showed that at stations 6-7, the color of the water was murky and blackish and caused a pungent odor. The average width and height of the river were 7.82 m and 48.49 cm, respectively. The substrate type of stations 1-6 is dominated by rocky sand while muddy sand at station 7. The average TSS value of 0.0399 mg/l and pH value of 8.65 showed that the value was in accordance with quality standards. DO values for stations 5-7, BOD at stations 6-7, and ammonia values for stations 4-7 do not meet quality standards. Community activities carried out are bathing, washing and disposing of garbage. Management efforts that have been carried out are rainwater harvesting, making biopore holes, waste banks, and river tracing. There are 6 management strategies with 16 programs for water quality management of Wai Batu Gajah.